Pacific economic monitor May 2019 special 10th Anniversary Issue. (Pacific economic monitor.)
The 10th edition features policy briefs focusing on the effects of climate change, impacts of natural hazards, income and purchasing power, service delivery, economic empowerment of women, and labor markets in the region.